2022
DOI: 10.14348/molcells.2022.2176
|View full text |Cite
|
Sign up to set email alerts
|

GATA2-Mediated Transcriptional Activation of Notch3 Promotes Pancreatic Cancer Liver Metastasis

Abstract: The liver is the predominant metastatic site for pancreatic cancer. However, the factors that determine the liver metastasis and the specific molecular mechanisms are still unclear. In this study, we used human pancreatic cancer cell line Hs766T to establish Hs766T-L3, a subline of Hs766T with stable liver metastatic ability. We performed RNA sequencing of Hs766T-L3 and its parental cell line Hs766T, and revealed huge differences in gene expression patterns and pathway activation between these two cell lines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…GATA2 is highly expressed in prostate cancer, pancreatic cancer, glioma, and colorectal cancer, and its overexpression promotes cancer cell proliferation, EMT, and cancer stemness; inhibits apoptosis; and increases tumorigenicity and resistance to standard therapies. 17,[44][45][46] High GATA2 expression is positively correlated with tumor stage, disease recurrence, and distal metastasis in prostate and colorectal cancer. [47][48][49] In the animal experiments in Figure 7B,D, we determined that the expression level of GATA2 was lower and the tumor volume was larger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GATA2 is highly expressed in prostate cancer, pancreatic cancer, glioma, and colorectal cancer, and its overexpression promotes cancer cell proliferation, EMT, and cancer stemness; inhibits apoptosis; and increases tumorigenicity and resistance to standard therapies. 17,[44][45][46] High GATA2 expression is positively correlated with tumor stage, disease recurrence, and distal metastasis in prostate and colorectal cancer. [47][48][49] In the animal experiments in Figure 7B,D, we determined that the expression level of GATA2 was lower and the tumor volume was larger.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported that GATA2 promotes cancer progression. GATA2 is highly expressed in prostate cancer, pancreatic cancer, glioma, and colorectal cancer, and its overexpression promotes cancer cell proliferation, EMT, and cancer stemness; inhibits apoptosis; and increases tumorigenicity and resistance to standard therapies 17,44–46 . High GATA2 expression is positively correlated with tumor stage, disease recurrence, and distal metastasis in prostate and colorectal cancer 47–49 .…”
Section: Discussionmentioning
confidence: 99%
“…Liver metastasis is the most common form of pancreatic cancer and is associated with poor prognosis. [25,26] In contrast, patients with pancreatic cancer and lung metastasis exhibit much longer survival. [27,28] In this cohort, the incidences of liver, lung, and lymph node metastases were 75.8%, 10.1%, and 10.4%, respectively.…”
Section: Pathology Metastasis and Multi-disciplinary Team Discussion ...mentioning
confidence: 99%
“…Pancreatic cancer is one of the most lethal tumor types, and novel therapeutic approaches against PDA should be developed to meet unmet clinical needs ( Jiang et al, 2022 ; Lin et al, 2022 ). Over the last decade, tumor energy metabolism has been a target for PDA therapeutics, but tumor metabolic plasticity has been behind their failure ( Jiang et al, 2022 ; Park et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%